Adherence to Inhaled Corticosteroid Treatment in Non-Atopic Children with Severe Recurrent Wheeze - Baraç, Raziye; Can, Demet; Uysal, Pinar; Gülle, Saniye; Asilsoy, Suna; Yazici, Selçuk; Bak, Mustafa (Global Journal of Respiratory Care, 2015)
Background: Recurrent wheeze is an important problem due to the probability of developing asthma. The treatment and adherence to therapy of recurrent wheezing in infants remains controversial. Objective: The present study was designed to investigate the compliance to inhaled corticosteroids (ICSs) and the response to the therapy in non-atopic children with severe recurrent wheeze. Methods: The non-atopic children with a severe recurrent wheeze who admitted to Behçet Uz Children Hospital were recruited to the study. The subjects practiced the skills to use ICSs and were followed-up for the adherence to ICSs following 6 months. Results: One hundred and six children diagnosed as non-atopic severe recurrent wheezers participated to the study. The mean age of the children was 22.0±15.4 months. The compliance rate to the treatment was 33.9%. The expectations of parents about beneficial effects of the medication were not met in 59 patients (84.2%) in early treatment cessation group. There was a significant difference between the treatment compliant patients and the patients with early treatment cessation among the experience of benefit in reduction of exacerbation days and exacerbation frequency, number of cough and sleep deprivation (p=0.002, p=0.004, p=0.002, respectively). The most common reason for early treatment cessation was the parents’ belief of the inefficiency of the medications on their ‘non-asthmatic children’. Discussion: Adherence to treatment with inhalers falls behind the expectations in severe recurrent wheezers. We suggest that, the physicians should participate to understand the barriers and concerns about regular treatment usage to increase compliance and prevent future development of asthma.